The Effect of Energy Consumption Towards Economic Growth: The Case of 11 Asian Countries - Susilo, Yuvensius Sri; Kartawinata, Matthew; Herawan, Jonathan Ersten (International Journal of Energy Economics and Policy, 2024)
This research aims to determine and analyze the effect of Coal Consumption per capita (Kwh), Oil Consumption per capita (Kwh), Gas Consumption per capita (Kwh), and Renewable energy consumption per capita (Kwh) towards GDP per capita (current US). This research uses GDP Per Capita (current USD) data sourced from world banks with a period from 1994 to 2021 and Data for Coal Consumption per capita (Kwh), Oil Consumption per capita (Kwh), Gas Consumption per capita (Kwh), and Renewable energy consumption per capita (Kwh) from Our Wold within a period from 1994 to 2021. The data used is data from 11 Asian countries, which is Mainland China, The Republic of Korea, Japan, India, Bangladesh, Pakistan, Thailand, Indonesia, Malaysia, Philippines, and Viet Nam. The analysis method used is Panel Data Econometrics, with Ordinary Least Square and Fixed Effect Model. The result from this research shows that Oil Consumption per capita (Kwh), Coal consumption per capita (Kwh), Gas Consumption per capita (Kwh), and Renewable energy consumption per capita (Kwh) have a positive significant effect towards GDP per capita (current USD).